Do Religious People Have More Children? The Effect of Religious Affiliation and Religiosity on Fertility - Halimatusa'diyah, Iim; Toyibah, Dzuriyatun (Journal of Population and Social Studies [JPSS], 2021)
This paper aimed to examine the effect of religious affiliation and religiosity on the fertility rate. While scholars have predicted the decline of religion’s influence, practice, and role in modern societies, religion still plays a vital role in shaping individuals’ behavior, including their fertility behavior. While there have been many studies on the role of religion on fertility, few studies have compared the fertility rates among people from different religious affiliations and their practices of religiosity. Additionally, cross-national analyses of the fertility rate of religious individuals who live as a majority or minority in various countries are still limited. Drawing from the World Value Survey data and using OLS regression to examine interaction and socialization, and minority-status approaches to the relationship between religion and fertility behaviors, this study revealed that Muslims are more likely to have a higher number of children among the explored religions. In terms of religiosity, those who are more religious, from all religious affiliations, demonstrated the same likelihood of having high fertility. Additionally, while both ritual and belief dimensions of religiosity are significantly associated with a high fertility rate for all religious affiliations, all dimensions of religiosity had significant effects on fertility for Muslims. Furthermore, Muslim and Christian minorities were likely to have lower fertility rates than their counterparts with majority status.